SCIENTIFIC IMPACT INDICATORS: A COMPARATIVE STUDY OF BRAZILIAN JOURNALS' IMPACT FACTORS - Almeida, Catia Candida de [UNESP]; Cabrini Gracio, Maria Claudia [UNESP]; Rafols, I; MolasGallart, J.; CastroMartinez, E.; Woolley, R. (Univ Politecnica Valencia, 2016)
In this context science social, this study aims to compare the IF of Brazilian journals, simultaneously present in Scopus and SciELO databases, in order to contribute to the discussion on the need to contextualize the use of IF as a quality indicator of scientific journals for the science denominated peripheral. The choice of multidisciplinary database Scopus is justified as this basis presents the highest number of indexed Brazilian journals.